On ?m-Asymptotically Deferred Statistical Equivalent Sequences of Order ? - Et, Mikail; Cinar, Muhammed; Sengul, Hacer (Univ Nis, Fac Sci Math, 2019)
In this study we introduce and examine the concepts of Delta(m)-asymptotic deferred statistical equivalence of order alpha and strong Delta(m)-asymptotic deferred equivalence of order alpha of sequences of real numbers. Also, we give some relations connected to these concepts.
Keywords: Deferred statistical convergence; asymptotic statistical equivalence; difference sequences